Production and Transport of Supraglacial Debris: Insights From Cosmogenic 10Be and Numerical Modeling, Chhota Shigri Glacier, Indian Himalaya - Scherler, D.; Egholm, D. L.; 3 Department of Geoscience Aarhus University Aarhus Denmark (Journal of Geophysical Research: Earth Surface, 2020)
Plain Language Summary High and steep mountain ranges are currently undergoing changes due to increasing temperatures. These changes include rapidly shrinking glaciers as well as thawing permafrost, which together destabilize rock walls that surround valley glaciers. In consequence, slope failures and thus erosion rates in these environments are expected to increase. However, quantifying rock wall erosion in alpine landscapes is difficult and estimates of background erosion rates that are unaffected by Global Warming are rare. Here we estimate rock wall erosion rates above the Chhota Shigri Glacier, Indian Himalaya, by studying rocky debris from the glacier surface. This debris is sourced from the surrounding topography and we use geochemical tools to measure its residence time at the Earth surface. We combine our geochemical observations with a computer model of the glacier that allows us to explore the effect of Global Warming on the evolution of the glacier and the debris on its surface. Our results suggest recent changes in rock wall erosion rates that may be related to glacier retreat and an increase in the erosion of rock walls that were previously ice covered. Key Points 10Be‐derived headwall erosion rates are ~0.5–1 mm year−1 on average and apparently increasing toward the present We use ice modeling to explore the effects of transience and spatial variability in erosion rates and source areas on 10Be concentrations Potential explanations for the observed trend in 10Be concentrations include enhanced erosion of recently deglaciated areas Deutsche Forschungsgemeinschaft (DFG) http://dx.doi.org/10.13039/501100001659 EC | H2020 | H2020 Priority Excellent Science | H2020 European Research Council (ERC) http://dx.doi.org/10.13039/100010663